VEHICLE TRAFFIC VOLUME ANALYSIS DUE TO SOUND GENERATED IN FRONT OF THE RS. Hermina Bogor - Syaiful, Syaiful; Prayudyanto, Muhammad Nanang; Rulhendri, Rulhendri; Lestari, Puri Anita; Nabila, Aqies Naili; Damiana, Salma Leandra; Haldiana, Haldiana (ASTONJADRO, 2022)
Motorcycles produce a variety of sounds. Sound is synonymous with noise. Noise is big enough to have an impact on the comfort of a place that is directly related to the highway. The distance between the hospital building and the road must be taken into account. This distance is important for the realization of patient comfort in the hospital/treatment room. The volume of motorcycles, light vehicles and heavy vehicles must be controlled, especially those passing through schools/places of worship/hospitals. Traffic flow/volume of motorcycles, light vehicles and heavy vehicles have a significant effect on noise. The calculation results obtained the largest equation on the fourth day of research at the third point (sound level meter2), with a contribution of 34.22% at y = 59.11 + 0.3x1 - 0.1x2 - 0.17x3. This equation means that if there is no decrease in the volume of motorcycles, light vehicles and heavy vehicles, the noise level in SLM2 is 59.11dBA. If there is an increase in the volume of motorcycles, light vehicles and heavy vehicles, the noise significantly affects. The results of the second equation from the calculation of the first day at the third point (sound level meter3) with a contribution of 19.30% based on the equation, y = 60.54 + 0.01x1 – 0.01x2 + 0.08x3. This means that if there is an increase in the volume of the motorcycle, the noise on the SLM3 is 60.54dBA. From the results obtained, there has been a decrease in the volume of motorcycles, light vehicles and heavy vehicles that pass through RS Hermina Bogor during the Covid-19 pandemic, because many hospital visitors/users do not travel or self-isolate at home. Decrease in the number of motorized vehicles that pass in front of the hospital. RS Hermina Bogor reached 45%.